EFEKTIVITAS LATIHAN PERNAFASAN RELAKSASI TERHADAP KELELAHAN PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI - Vervando Janter Sumilat; Prabawati Prabawati; Sudibyo Supardi (Jurnal Ilmiah Perawat Manado (Juiperdo), 2020)
Abstract Background: Cancer patients with chemotherapy experience fatigue as cancer effects and cell destruction due to the toxicity of chemotherapy drugs. Objective: Determine the effectiveness of relaxation breathing exercises to fatigue cancer patients who undergoing chemotherapy. Methode: This research used quasi experiment pretest and posttest method. There were 92 respondents who examined using purposive sampling technique and divided into 46 respondents as intervention group and 46 respondents as control group. Relaxation breathing exercise was given four weeks for intervention group on April-July 2018 in Siloam Hospital Manado. Result: The majority of cancer patients were age 45-65 years 69,9%, 54,3% were diagnosed cancer ≤1 year and 79,3% received combination chemotherapy. The result of Wilcoxon test revealed there was significant difference before and after intervention to fatigue (p value = 0,00), with mean rank of reduction 21,97% on fatigue. The result of Mann Whitney test revealed that there was significant difference in fatigue between intervention and control groups (p value = 0,00). Multivariate logistic regression revealed that there was an effect of relaxation breathing exercise on fatigue (p value = 0,00) and relaxation breathing exercise may reduce 60,46 times of fatigue on patients who undergoing chemotherapy. Conclusion: Relaxation Breathing Exercise can reduce fatigue in cancer patients who undergoing chemotherapy in Siloam Hospital Manado. It is recommended to perform relaxation breathing exercise as a routine exercise for cancer patients during chemotherapy to minimize fatigue. Keywords: Relaxation Breathing Exercise, Fatigue, Chemotherapy, Cancer